Constructivist Security Studies: Portrait of a Research Program - Farrell, Theo (International Studies Review, 2002)
The traditional focus on power and politics in security studies has been robustly challenged this decade by the development of two ideational approaches to the subject: constructivism and culturalism. The first section briefly examines these two literatures, considers how they have differed in the past, and suggests how they may now form a coherent constructivist research program. Section two clears up two common misconceptions about constructivism in security studies-namely, that it does not have a positivist epistemology but has a normative agenda. Constructivists do seek to explain the world (according to rules of social science) but not to change it. Section three addresses the criticism that a positivist epistemology is inconsistent with an ontology that gives causal weight to cultural variables. The final section concludes by discussing two options-one confrontational, the other cooperative-for a constructivist engagement of realism (the dominant approach in North American security studies).